Engineering contributions to the life sciences. - Geddes, L.A.
This paper discusses the contributions that physicians have made to the physical sciences. Some of the physicians mentioned by the author are William Gilbert who gave the first accurate treatise on magnetism, Thomas Young who gave us Young's modulus was also the first to discover the interference of light waves, Luigi Galvani who started the study on current electricity and bioelectricity, and Jean Louis Marie Poiseuille who was first to measure aortic pressure in dogs using a mercury U-tube manometer
Keywords: Young modulus; Aortic pressure; Bioelectricity; Current electricity; Engineering contributions; Life sciences; Light wave interference; Magnetism; Mercury U-tube manometer; Physical sciences; Physicians